A STUDY ON FACTORS INFLUENCING INTERPERSONAL SKILLS OF SALES PROFESSIONALS IN SERVICE INDUSTRY (International Journal of Food and Nutritional Sciences, 2022)
Service industry has shown significant growth in India and the world respectively. The motivation behind this study is to investigate the factors that influence interpersonal skills among sales professionals working in the service business. More specifically, the study focuses on how different demographic and professional characteristics influence particular aspects of interpersonal effectiveness. This research makes use of a comprehensive survey instrument to investigate a number of different factors, such as age, gender, education, marital status, family background, wage, experience, rural-urban status, communication skills, and personality type. As a result of the investigation, it has been determined that the most significant predictors of interpersonal performance in sales roles are communication skills, marital status, and personality type. Besides, the findings of the study indicate the importance of productive communication, secure personal circumstances, and adequate personality qualities in request to work on interpersonal skills. These skills, in turn, influence professional outcomes such as confidence, negotiating, concept presentation, and relationship management. In order to evaluate the influence of these elements, the research makes use of regression analysis and analysis of variance (ANOVA), which demonstrates a high level of explanatory power and internal consistency. In addition to providing useful insights into the major drivers of interpersonal success in sales, this detailed investigation also offers concrete implications for training and development programs that are targeted at enhancing sales performance in the service business.